The effects of subcontracting/outsourcing on occupational health and safety - Mayhew, Claire; Quinlan, Michael; Bennett, Laura (University of New South Wales, 1996)
A research study was designed to shed light on the impact of the outsourcing of labour on Occupational Health and Safety (OHS) indices. Over 250 workers in Child Care, Hospitality, Transport and Building were interviewed and completed a questionnaire. After collation of the data, direct comparisons between the self-employed/subcontract and employee workers were made. It was found that in situations where the outsourcing of labour has become common, working conditions generally - as well as OHS - deteriorated for both the subcontract and the employee workers. At the same time, the OHS of self-employed workers was placed even more at risk. A number of recommendations have been made which could control the negative OHS consequences from the outsourcing of labour.